Middlemore Hospital experience with tubo-ovarian abscesses: an observational retrospective study - Habboub AY (Dove Medical Press, 2016)
Antoine Youssef Habboub Middlemore Hospital, Counties Manukau District Health Board, Auckland, New Zealand Aim: The aim of this paper was to study the characteristics of patients presenting to Middlemore Hospital with tubo-ovarian abscess (TOA) and to compare the outcomes of conservative medical management versus medical management with surgical drainage and medical management with radiological drainage.Methods: All patients admitted with a radiologically or surgically proven TOA between January 01, 2008 and December 31, 2010, were included and followed up until June 30, 2011. The total number of patient/index admission was 174.Results: The mean age of patients was 37.8 years. One hundred thirty patients had medical treatment only with hospitalization and antibiotics, and 44 patients were managed with antibiotics and surgical drainage. Complete resolution of TOA was 77.3% (99/128) for patients managed medically and 93.2% (41/44) for patients managed surgically. When the two groups were compared, patients who were managed surgically were more likely to have complete resolution of TOA within 6 months of index admission with an odds ratio (OR) of 4 and a P-value of 0.029. There was no statistically significant difference in the secondary outcomes namely of readmission with TOA (OR: 0.47) and the need for repeat surgical or radiological drainage (OR: 1.48). Nonetheless, the relative duration of hospitalization was longer for the surgical group with a P-value of <0.0001. The C-reactive protein and the size of TOA were the significant factors involved in the resolution of TOA.Conclusion: The results of this study confirmed our initial hypothesis that we should consider surgical drainage more often, probably earlier, especially for the younger patients still desiring fertility preservation and for larger abscesses. Laparoscopic surgical drainage is safe and could be used as the procedure of choice. Conservative medical management is still acceptable with good cure rates of 77%. C-reactive protein and the size of the abscess were the important factors to consider when managing patients with TOA. Keywords: tubo-ovarian abscess, pelvic inflammatory disease, antibiotics, surgical drainage